Constitutional identity in a Europe of multilevel constitutionalism / edited by Christian Calliess, Gerhard van der Schyff. - Calliess, Christian, 1964-; Van der Schyff, Gerhard (Cambridge University Press, 2020)
The constitutional identity of the Member States is a topic of increasing importance in understanding the interaction between the EU and its Member States. This is because the EU is enjoined to respect the constitutional identities of its Member States in accordance with Article 4(2) TEU. There is also a trend among Member States to articulate their constitutional identities, in particular in relation to European integration. In this regard, this volume fills a need in scholarship by presenting critical analyses of the constitutional identities of selected Member States. Leading and well-placed experts contribute country studies on a range of states, which are compared using a framework that can be applied to other Member States as well. The analyses and comparison of Member States' constitutional identities take place in the context of the EU's multilevel architecture.